1994
DOI: 10.3758/bf03213969
|View full text |Cite
|
Sign up to set email alerts
|

Amsel’s analysis of reward-schedule effects

Abstract: Some questions raised by Amsel's valuable review of his extensive research on reward-schedule effects are considered-questions about the nature of instrumental conditioning, about the distinction between long-and short-term memory, and about evolutionary divergence in learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is tempting instead to propose a supplementary mechanism that enhances the attractiveness ofa location at which reward has been found (and perhaps of the color found there as well) for a briefperiod thereafter-a recency or short-term memory effect-such as has been suggested to deal with some analogous results for pigeons (Bailey & Mazur, 1990). In view of the evidence of divergence that has appeared in comparative experiments on the control ofperformance by short-term memory of reward and nonreward in vertebrates (Bitterman, 1994), the study of short-term memory in honeybees promises to be particularly instructive. For further work on the problem, it will be necessary to modify the training situation in such a way as to remove the previously reinforced color before each new choice can be made, and to permit (both in color and in location experiments) exact control ofthe time between the experience to be remembered and the subsequent opportunity for choice.…”
Section: 60mentioning
confidence: 99%
“…It is tempting instead to propose a supplementary mechanism that enhances the attractiveness ofa location at which reward has been found (and perhaps of the color found there as well) for a briefperiod thereafter-a recency or short-term memory effect-such as has been suggested to deal with some analogous results for pigeons (Bailey & Mazur, 1990). In view of the evidence of divergence that has appeared in comparative experiments on the control ofperformance by short-term memory of reward and nonreward in vertebrates (Bitterman, 1994), the study of short-term memory in honeybees promises to be particularly instructive. For further work on the problem, it will be necessary to modify the training situation in such a way as to remove the previously reinforced color before each new choice can be made, and to permit (both in color and in location experiments) exact control ofthe time between the experience to be remembered and the subsequent opportunity for choice.…”
Section: 60mentioning
confidence: 99%
“…According to the sequential model, instrumental performance is controlled both by memories of prior events and representations of anticipated events (see e.g., Capaldi 1994a). Capaldi (1994b) suggested that learning models that emphasize both memory and anticipation are becoming increasingly popular (see also, Amsel 1994;Bitterman 1994).…”
Section: Dlstra 9 Intervalmentioning
confidence: 99%